Growth hormone treatment associates with improved circulating anti-aging protein Klotho and reduced arterial stiffness in children with CKD - Stabouli, Stella; Leifheit-Nestler, Maren; Föller, Michael; Feger, Martina; Bayazit, Aysun K; Doyon, Anke; Obrycki, Lukasz; Ranchin, Bruno; Oh, Jun; Paripovic, Dusan; Longo, Germana; Harambat, Jerome; et al. (Clinical kidney journal, 2025)
Chronic kidney disease (CKD) is characterized by low levels of the anti-aging protein α-Klotho and accelerated cardiovascular (CV) morbidity. Short-term treatment with growth hormone (GH) was shown to enhance soluble Klotho (sKlotho), the circulating form of α-Klotho, and endothelial function in patients with CKD. We hypothesized that long-term GH treatment in pediatric patients with CKD improves sKlotho levels and CV morbidity.We performed a case-cohort study within the Cardiovascular Comorbidity in Children with Chronic Kidney Disease (4C) study including 101 children with CKD stages 3-5 treated with and without GH. Patients were assessed for serum sKlotho, intact fibroblast growth factor 23 (iFGF23), somatomedin insulin-like growth factor 1 (IGF1), pulse wave velocity (PWV), carotid intima thickness (cIMT), and left ventricular mass index (LVMI) at two time points 12 months apart.GH-treated patients showed higher sKlotho (Δ1.2 SD) and IGF1 (Δ1.5 SD) z-scores, and lower PWV z-scores (Δ −0.9 SD) compared to controls (each P < .01), both at baseline and after 12 months of follow up. iFGF23 and cIMT z-scores, LVMI, and progression of CKD did not differ between groups. In the multivariable analysis, sKlotho z-scores associated with GH treatment, IGF1 and iFGF23 z-scores (each P < .01). PWV z-scores associated with GH treatment, diastolic blood pressure, and parathyroid hormone levels, while cIMT z-score and LVMI associated with diastolic blood pressure and hemoglobin only (each P < .05).Long-term GH treatment is associated with reduced PWV in children with CKD, which is at least partly related to GH/IGF1-induced upregulation of sKlotho.
Gesehen am 18.02.2026